How do you solve this logarithmic equation?

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

loga(x-1) - loga(x+6) = loga(x-2) - loga(x+3)

I am stuck at the part when I put them in a division equation:  x-1/x+6 = x-2/x+3

Dec 3rd, 2014

(x-1)/(x+6) = (x-2)/(x+3)

Both sides multiply (x+3)(x+6)

(x-1)(x+3)=(x-2)(x+6)

x^2+2x-3=x^2+4x-12

2x-3=4x-12

12-3=4x-2x

9=2x

x=9/2

Dec 3rd, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Dec 3rd, 2014
...
Dec 3rd, 2014
Oct 21st, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer